KUALITAS FISIK SILASE BUAH SEMU JAMBU METE PADA BERBAGAI LEVEL TEPUNG GAPLEK DAN LAMA PEMERAMAN - Bernadete Barek Koten (Partner, 2010)
Physical Quality of cashew (Anacardium occidentale) pseudocarp (the pear-shaped fruit of the cashew) Silage in Combination with Various Levels of Cassava Mill Addition and Length of Fermentation. The aim of this experiment was to evaluate physical quality of cashew pseudocarp silage in combination with various levels of cassava mill addition and length of fermentation. This study was designed with a factorial completely randomized design in two treatment factors with three replications. The first factor was various level of cassava mill i.e. L1: 0%, L2: 3%, L3: 6%, and L4: 9%, and the second factor was length of fermentation i.e. W1: 20 days, W2: 40 days and W3: 60 days. The result showed that the cassava mill levels and the length of fermentation did not affected to the damage and decrease level of cashew pseudocarp silage (P>0.05) but it affected to the level of acidity (P>0.01). The physical quality of cashew pseudocarp silage was very good with the damage level average was 1.19%, and the decrease level average was 6.87%. The level of acidity ranged from 3.72 to 4.14. The lowest acidity level was at L4W1 (3.72) and the highest one was at L2W2 (4.14) with the average of acidity was 3.93. Thus, it can be concluded that the best physical quality of cashew pseudocarp silage was at 9% level of cassava mill with 60 days of fermentation length. However, all treatment combinations of cassava mill level and fermentation length produced high physical quality of silage.Keywords: physical quality, pseudocarp, cashew, cassava mill, fermentation, acidity